Cross-border timber trade in Indonesia: critical or overstated problem? Forest governance lessons from Kalimantan - Obidzinski, K.; Andrianto, A.; Wijaya, C. (2007)
Illegal logging has been at the centre of policy debates about the current state and future prospects of Indonesia’s forestry sector. One of the prevailing views is that clandestine cross-border timber trade is responsible for illegal logging in the country. This paper shows the core of the illegal logging problem lies not in timber smuggling in remote locations but in licensed forestry operations that engage in gross overharvesting and violate shipping regulations. These actions, in turn, are necessitated by a vast supply-demand disparity in Indonesia’s woodworking sector. The current timber trade system in Indonesia that stresses administrative and document compliance is insuffi cient because it is easy to manipulate and its enforcement is lax. Therefore, there is an urgent need for a more stringent timber legality standard that would be simpler to enforce and easier to evaluate. However, this will only work if a serious effort is made to restructure (downsize) forest industries and develop sustainable industrial timber plantations.